Electric Power Market: Competition in the Conditions of Global Change and Digitalization - Valentin Ya. Afanasyev; Vladimir F. Ukolov; Vitaliy V. Kuzmin (International Journal of Supply Chain Management, 2019)
Abstract- The present paper examines the actual prob-lem of changing conditions of competition in the elec-tricity market, considering the peculiarities of its de-velopment in the context of global changes and digi-talization. This study is aimed at developing ap-proaches to mitigate state and interstate regulation of the development of competitive market conditions through the creation of prerequisites for freer compe-tition. The authors analyze the features of the electrici-ty market based on the special nature of the electro-magnetic processes in electrical circuits, obeying objec-tive physical laws, causing the technological features of the process of production, as well as transmission and consumption of electrical energy. It is shown that the features of this market, including the active devel-opment of digitalization, have a serious impact on the creation of conditions for freer com-petition. In order to improve the efficiency of the electricity supply sec-tor, the necessity of re-forming the conditions of com-petition in the electricity market is justified regarding the use of digitalization as a tool to improve the indus-try’s technological processes. The materials of the present paper are of practical value for various organ-izations engaged in business in the field of electricity, the functioning of digital enterprises, government agencies, as well as specialists in the electric power industry. The approaches formulated in the paper can be used in practice in the development and im-plementation of a new set of measures to develop competitive conditions in the studied market, making management decisions based on digital technology, big data and artificial intelligence.